Sustainable control of bagworm (Lepidoptera: psychidae) in oil palm plantation: a review paper - Muhamad Syukrie Abu Talip (2024)
The oil palm industry is a key economic agriculture activity to contribute to Malaysia Gross Domestic Product (GDP). In 2019, it was reported that oil palm GDP was about RM38 Billion or 38% of the agricultural sector in Malaysia. However, the substantial yield reduction due to pest attacks are becoming main threats in the oil palm industry. The bagworm (Lepidoptera: Psychidae) is one important leaf eating pest that could cause severe leaf damage and yield losses up 43% without a proper treatment as stated by Malaysia Oil Palm Board (MPOB) in 2016. Integrated pest management (IPM) has been suggested in pest control measures by integrating various techniques such as biological controls, cultural controls, and chemical controls. Insect natural enemies consist of predators as a biological control agent that capture and feed on bagworm thus reducing the infestation outbreaks. The establishment of ground vegetation flowers such as beneficial plants able to increase the insect natural enemies’ population as a part of cultural controls. The presence of beneficial plants would provide nectar as a food source for predators. Chemical controls have been identified as an effective measure to reduce the incidence of bagworm in oil palm estate. The application of insecticides through Trunk Injection (TI) and aerial spraying are fast-acting to reduce the larval population of bagworm. The investigation of pheromone traps was carried out for trapping of male bagworm moths thus reducing the subsequent population of larvae due to reducing chances of mating. This paper deliberates on controlling the bagworm population through integrated pest management (IPM) that ensures sustainable control of bagworm in oil palm plantation.